Healthy lifestyle patterns and mental health among university students: a systematic literature review - Eldi Pratama; M. Fahli Zatrahadi; Miftahuddin (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2026)
Mental health problems among university students have become a critical global public health concern. Unhealthy lifestyle behaviors are strongly associated with elevated psychological distress in this population. However, comprehensive synthesis examining the multidimensional relationship between healthy lifestyle patterns and student mental health remains limited. This systematic literature review aimed to (1) identify the most frequently studied components of healthy lifestyle in relation to university student mental health, and (2) synthesize evidence on the relationship between healthy lifestyle patterns and mental health outcomes, including psychological well-being, stress, anxiety, depression, and emotional well-being. A systematic search was conducted across PubMed, Scopus, Web of Science, and PsycINFO databases. Studies published between 2022 and 2025 were included. Inclusion criteria required empirical studies focusing on college or university students, healthy lifestyle components, and mental health outcomes. The PRISMA 2020 framework guided the review process, and thematic narrative synthesis was applied to analyze extracted data. Quality appraisal was conducted using JBI Critical Appraisal tools. Twenty peer-reviewed studies were included in the final synthesis. Six dominant lifestyle themes emerged: physical activity, sleep quality, diet and nutrition, social support, general health behaviors, and sedentary/screen time behavior. Physical activity and sleep quality were the most consistently studied components. Across RQ2, healthy lifestyle patterns demonstrated protective associations with psychological well-being, and significant inverse relationships with stress, anxiety, depression, and negative emotional states. Sleep quality emerged as the single most consistently influential factor across all mental health outcomes. Healthy lifestyle patterns, particularly regular physical activity, adequate sleep, balanced nutrition, and strong social support, are positively and consistently associated with better mental health outcomes among university students. Universities should integrate holistic health promotion programs addressing multiple lifestyle dimensions simultaneously.